Use substitution:
Multiply 2nd equation by 3
9x+3y=15
Add to first equation
11x=22
x=2
Substitute into second equation
3(2)+y=5
y=-1
2007-03-06 19:48:52
·
answer #1
·
answered by iron_composite 4
·
1⤊
0⤋
First there are three different methods of solving simultaneous equations they include the substitution method, the elimination method and the graphical method.
I would use the elimination method because I feel it's the simplest;
Let's name the equations as 2x-3y=7-----(1) & 3x+y=5------(2)
multiply equation (1) by 1 and equation(2) by 3 to give
2x-3y=7-----(1)
9x+3y=15-----(2)
then add equation (1) from equation (3) to give
11x + 0=22
x = 22/11
x=2
To get y from equation (1)
2x-3y=7 substitute the value of x in the equation
2*2-3y=7
4-3y=7
4-7=3y
-3=3y
y=-3/3
y=-1
2007-03-07 03:58:17
·
answer #2
·
answered by Samuel_007 2
·
1⤊
0⤋
Multiply 1st equation by 1 and 2 nd equation by 3:-
2x - 3y = 7
9x + 3y = 15---------ADDING gives:-
11x = 22
x = 2
Substituting for x = 2 gives: -
6 + y = 5
y = - 1
Solution is x = 2, y = - 1
2007-03-07 06:19:48
·
answer #3
·
answered by Como 7
·
1⤊
0⤋
2x-3y=7
3x+y=5
y = 5 - 3x
2x - 3(5-3x) = 7
2x - 15 + 9x = 7
11x = 7 + 15
x = 22/11
x = 2
y = 5 - 3x
y = 5 - 3(2)
y = 5 - 6
y = -1
Answer: (x, y) = (2, -1)
><>
2007-03-07 07:46:28
·
answer #4
·
answered by aeiou 7
·
1⤊
0⤋
2x-3y=7
3x+y=5
multiply the 2nd equation by 3
9x+3y=15
Add the 2 equations.
11x+0y=22, x=2
So 6x+y=5
So y=-1
2007-03-07 03:44:53
·
answer #5
·
answered by verbalise 4
·
1⤊
1⤋
2x-3y=7-----(1)
3x+y=5 -----(2)
frm 1,
2x=3y+7
x=(3y+7) / 2-----(3)
sub (3) into (2)
3[(3y+7) /2]+ y = 5
[(9y+21) / 2] + y =5
multiply the whole equation by two to clear denominator
9y+21+2y=10
11y+21-10=0
11y=11
y=1
sub y=1 into (1),
2x-3y=7
2x-3(1)=7
2x=10
x=5
=) mine is the correct answer
2007-03-07 03:58:38
·
answer #6
·
answered by yuki 2
·
0⤊
2⤋